(untitled) (Journal of Human Sciences, 2021)
This study deals with the French policy in the Fezzan region after the Second World War, and the Fezzan region is considered one of the important areas that France has sought to control since the nineteenth century. The region has isolated the region from other Libyan regions and part of it from it, and travel permits have been imposed on every citizen leaving or entering the region, in addition to imposing a special currency in the region, and when the war ended and in the midst of international changes that prevailed in the world after that, France entered into conflict with the major countries And the United Nations in an attempt to remain in the region, but the national elites fought for the independence of Libya and the unity of its regions and succeeded in that.